Multi-rotor reluctance machine - Misron, Norhisam; Raja Nor Firdaus,; Vaithilingam, Chockalingam Aravind (2013)
This invention is about multi rotor reluctance motor (100) used in servo positioning, control and electric drive system applications. This developed motor (100) is intended for high torque and low speed applications. It consists of plurality of rotor structures (12a, 12b, 12c) and one or more stator (10a, 10b), said plurality of rotors (12aq, 12b, 12c) concentrically disposed and aligned to a central axis thereof such as to favourably distribute the air gap there between the rotor (12a, 12b) and stator (10a, 10b) thereby increasing the flux density and developing higher torque.